FEASIBILITY TEST OF COOPERATIVE GI (GROUP INVESTIGATION)-BASED STUDENT WORKSHEETS (LKPD) ON STATIC FLUID MATERIAL - Dwi, Elfi; Panjaitan, Margaretha; Zamhir, Rizky; Sondang, Ruth; Megalina, Yeni (Journal of Learning and Technology in Physics, 2024)
This development research aims to produce physics LKPD based on Cooperative GI on the subject matter of Static Fluid which is feasible to be applied in the physics learning process at school and determine the response of students after using the developed LKPD.The subjects in this study were students of class XI MIPA totaling 18 students. This type of research is a development research or Research and Development (R&D) using the 4D Model. The instruments used in this study consisted of a validation questionnaire for material experts and learning experts, a questionnaire for the assessment of physics teachers, and a questionnaire for students' responses to the physics LKPD based on cooperative learning. The data analysis technique used in this research is descriptive. From the results of data analysis obtained material expert validation of 82%, learning experts 81%, physics teacher assessment of 90% with each of these percentages included in the very good category. While in the broad trial the percentage of student responses with a sample of 15 people was 86.06% with very good criteria, so that based on the results of validation, physics teacher assessment and student responses it can be concluded that Cooperative-based physics LKPD on the subject matter of Static Fluid is feasible to use in the learning process. Keywords: Development, LKPD, STEM, Elasticity and Hooke's Law